Dampak Pembangunan Jalan Poros Pariwisata Kendari-Toronipa Terhadap Masyarakat Bajo di Desa Leppe Kecamatan Soropia Kabupaten Konawe - Muhammad Olland Efendi; Rahmat Sewa Suraya (JURNAL KABANTI: Kerabat Antropologi, 2023)
The purpose of this research is to identify and describe the ecological impact that has occurred on the Bajo community in Leppe Village, Soropia District, Konawe District with the construction of the Kendari-Toronipa tourism axis road and to describe or determine the social impact that has occurred on the Bajo community in Leppe Village, Soropia District, Konawe District. using a qualitative approach with three ways of triangulation, namely conducting observations directly involved in the field, interviewing informants and field notes to obtain as much data as possible. Based on the results of the research, the ecological and social impacts on the Bajo community are due to the construction of the Kendari-Toronipa tourism axis road. Both of these impacts affect the activities of the Bajo community due to environmental changes and the lack of government policies in managing the resources of the fishing community so that it affects the fishing community and the social community of the Bajo. The benefits of the Kendari-Toronipa tourism axis road are superior tourism development and mobility.